Výkon sociální prevence u dětí a mladistvých na místní úrovni - Hůlová, Gabriela (Univerzita Pardubice, 2007)
Social prevention is implemented on several levels – on national, regional, and local level. Community is especially involved in social prevention on local level, trying to create effective prevention programmes on the base of direct knowledge of the local community needs. Important factors in this area are: legislative implementation and close cooperation of municipality and non-governmental unprofitable sector, especially organizations which deal with children and teen-agers. However, these factors are not realised ununiformly using standardized methods of social prevention. Main purpose of this work is to provoke expert discussion on ununiformity approach of social prevention on local level.
Keywords: social prevention; prevention programmes; local community; unprofitable sector; municipality; methods of social prevention